Behavior-Based Fuzzy Control for Mobile Robot Navigation. (21st September 2013) - Mo, Hongwei; Tang, Qirong; Meng, Longlong
Abstract : A new behavior-based fuzzy control method for mobile robot navigation is presented. It is based on behavioral architecture which can deal with uncertainties in unknown environments and has the ability to accommodate different behaviors. Basic behaviors are controlled by specific fuzzy logic controllers, respectively. The proposed approach qualifies for driving a robot to reach a target while avoiding obstacles in the environment. Simulation and experiments are performed to verify the correctness and feasibility of the proposed method.